Optimizing Student Learning Outcomes: The Role of School Environment in Islamic Elementary Schools - Dyah Arti Mumpuni; Harsono Harsono; Achmad Fathoni (STAI Hubbulwathan Duri, 2025)
The school environment plays a vital role in enhancing student learning outcomes, particularly in Islamic elementary schools where academic, social, and religious values are emphasized. A positive school climate can influence students' affective, cognitive, and skill development. This quantitative study investigated the impact of the school environment on student learning outcomes at Muhammadiyah Baitul Falah Elementary School. A total of 135 students from grades four to six participated. Data were collected using a Likert-scale questionnaire and analyzed through linear regression using SPSS version 26. The analysis revealed a significant positive relationship between the school environment and student learning outcomes. The regression analysis produced a significance value of 0.00 ( 0.05) and a regression coefficient of 0.570. These findings indicate that every unit improvement in the school environment correlates with a 0.570 unit increase in student learning outcomes. Key contributing factors included a supportive academic atmosphere, well-maintained physical facilities, and positive social interactions within the school community. The results highlight the importance of creating a conducive learning environment to support holistic student development in Islamic elementary schools. Enhancing school infrastructure, fostering positive interpersonal relationships, and encouraging a student-centered academic culture are essential strategies. While this study underscores the value of the school environment in shaping learning outcomes, it is limited to a single institution. Future research with broader samples is necessary to generalize these findings across other Islamic educational settings.